Designing control loops for linear and switching power supplies : a tutorial guide - Basso, Christophe P., ....- (Boston : Artech House, 2012)
Loop control is an essential area of electronics engineering that today's professionals need to master. Rather than delving into extensive theory, this practical book focuses on what you really need to know for compensating or stabilizing a given control system. You can turn instantly to practical sections with numerous design examples and ready-made formulas to help you with your projects in the field. You also find coverage of the underpinnings and principles of control loops so you can gain a more complete understanding of the material. This authoritative volume explains how to conduct analysis of control systems and provides extensive details on practical compensators. It helps you measure your system, showing how to verify if a prototype is stable and features enough design margin. Moreover, you learn how to secure high-volume production by bench-verified safety margins.
Basics of Loop Control -- Transfer Functions -- Stability Criteria of a Control System -- Compensation. Operational Amplifier-Based Compensators. Operational Transconductance Amplifier-Based Compensators -- TL431-Based Compensators -- Shunt Regulator-Based Compensators -- Measurements and Design Examples.
Includes bibliographical references and index.
Keywords: Switching power supplies -- Design and construction; Process control; Power electronics; Feedback control systems; Electric current converters